Exploring the current management of tuberculosis and diabetes mellitus amongst healthcare practitioners and patients: a qualitative study / Shahirah Mohd Nasir - Mohd Nasir, Shahirah (2015)
DM is the most common comorbidity in TB patients with prevalence as high as 15- 30% in Malaysia. The convergence of these two diseases is linked to poorer TB treatment outcomes, increased chances of relapse, reactivation of latent TB infection and higher risk of death during TB treatment. Realising this joint burden, World Health Organisation (WHO) and the International Union Against Tuberculosis and Lung Disease (The Union) have developed a provisional collaborative framework to guide national programmes, researchers, and those directly involved in the care, prevention, and control of TB and DM in order to establish a coordinated response to both diseases. In order to improve the provision of pharmaceutical care that is suited to every TB-DM patient, a thorough understanding of obstacles and limitations in the existing healthcare system must be attained. This study aims to explore the current management of TB and DM amongst healthcare practitioners and patients and seeks to unravel new ideas of creating awareness and imparting knowledge about the link between TB and DM amongst healthcare practitioners and patients. Data were collected through face-to-face interviews with healthcare practitioners and patients at Institut Perubatan Respiratori which were audio-recorded before being transcribed verbatim and analysed thematically. The pre-determined and emerging themes included the TB-DM management, directly observed treatment short-course (DOTS), knowledge about TB-DM link and barriers in healthcare system. The study revealed that the integration of DM management into the care of TB patients with DM comorbidity was still found to be lacking especially concerning DM monitoring in TB patients. DOTS visits were not utilised for DM monitoring due to time constraint and patient reluctance. Educational tools are imperative to educate both healthcare practitioners and patients effectively.